Enantioselective Cycloaddition Reactions Catalyzed by BINOL-Derived Phosphoric Acids and N-Triflyl Phosphoramides: Recent Advances - Felix E. Held; Dominik Grau; Svetlana B. Tsogoeva (Molecules, 2015)
Over the last several years there has been a huge increase in the development and applications of new efficient organocatalysts for enantioselective pericyclic reactions, which represent one of the most powerful types of organic transformations. Among these processes are cycloaddition reactions (e.g., [3+2]; formal [3+3]; [4+2]; vinylogous [4+2] and 1,3-dipolar cycloadditions), which belong to the most utilized reactions in organic synthesis of complex nitrogen- and oxygen-containing heterocyclic molecules. This review presents the breakthrough realized in this field using chiral BINOL-derived phosphoric acids and N-triflyl phosphoramide organocatalysts.